Economic system impacts and dependencies on water-related ecosystem services: defining analytical spatial units from an ecosystem accounting perspective in Guatemala - Pinillos, Daniel; Reyes, Paulina; Barrera, Valeria; Pineda, Pedro; Goyzueta, Juan Miguel; Schulte, Rogier; Castaneda, Juan-Pablo (Frontiers in Environmental Science, 2025)
Economic performance is traditionally assessed through the System of National Accounts (SNA), with Gross Domestic Product (GDP)—the annual aggregated market value of a country’s goods and services—as its most widely used indicator. However, economic sectors depend on resources and ecosystem services, placing pressures on ecosystem assets and biodiversity. It is well established that the SNA does not account for these complex interactions between economic activities and environmental systems. Accordingly, assessing the dependencies of economic sectors on ecological functions and natural resources is critical to support informed policy and decision-making. This study addresses this gap through a national case study in Guatemala, applying the System of Environmental-Economic Accounting (SEEA) framework. We employed the Integrated Valuation of Ecosystem Services and Tradeoffs (InVEST) suite of models to estimate water provision and sediment retention as key ecosystem services, alongside sediment export as a landscape disservice, at the river basin level. Official statistics, land use and land cover (LULC) data, and nighttime lights imagery were integrated to estimate GDP per basin. Based on these estimations of ecosystem services, disservices, and GDP per basin, we conducted a cluster analysis of Guatemala’s 62 basins, which resulted in five distinct typologies: (1) Boca-Costa and southeastern basins, (2) Metropolitan-highly urbanized basins, (3) Dry shrubland basins, (4) Forested upland basins with low economic activity and (5) Forested lowland basins with low economic activity. We propose these clusters as Ecosystem Accounting Areas (EAAs) under the SEEA framework. Finally, we developed water use intensity indicators per sector within each EAA. This integrated approach with ecological and economic data provides valuable insights for territorial governance and landscape multifunctionality at multiple scales in Guatemala.